Bioethanol production from disposed engine oil management - Makky, Essam A. (2018)
Disposed engine oil (DEO) is a recalcitrant carbon source for microorganisms as it is mainly composed of long chain saturated hydrocarbon. Hydrocarbon-degrading microorganisms from oil contaminated soil sample were successfully used for bioremediation of DEO. This research aims to study and bio-convert DEO and DEO contaminated soil to lipase enzyme and ethanol, which is common industrial waste that contain heavy metals which are harmful to environment and human health. Also to utilize and isolate microorganisms that is capable to degrade DEO and find the optimum parameters for the best lipase and ethanol production. Lipase production GS-3 bacterial isolate was successfully isolated from oil contaminated soil area. GC-MS analysis revealed that this isolate was able to produce organic acid, methyl-3, 4, 5-trimethoxy-2, 6-dinitrobenzoate from disposed engine oil. Besides, among the five solvents screened to extract the hydrocarbon present in the oil contaminated soil sample, toluene has the highest efficiency up to almost 0.041(μl/ml) of hydrocarbon which represent 93.3% of hydrocarbon from the sample. Therefore GS-3 isolate produced highest lipase activity, achieving 0.097 ± 0.007 U/ml/min during first 24 hours when disposed engine oil was used as carbon source. Data revealed new and broad band which is related to O-H stretching formed at 3421 cm-1, though new band occurred at 3424 cm-1 and 1645 cm-1 after bioremediation. While for ethanol production 1gm of DEO contaminated soil was added to 50ml of MSM medium and incubated for 10 days at 40ºC and pH 7. GC-FID analysis revealed that the soil mixed culture was able to produce ethanol from DEO contaminated soil through microbial fermentation. Subsequent Lipase optimization parameters revealed that this bacteria could produce the highest lipase activity 0.161±0.067 U/mL/min when the 4% (v/v) disposed engine oil was used as carbon source. The best nitrogen source was urea it was able to enhance lipase production up to 0.240±0.063 u/ml/min. In addition of surfactant Tween 80 could also enhance lipase production up to 0.221±0.001 U/mL/min. optimal pH value and temperature was 7.0 and 30°C has achieved 0.095±0.002, 0.125±0.013 U/mL/min respectively. Subsequent optimization of parameters for DEO degradation revealed that soil microorganisms able to biodegrade the oil by 69.23% under optimal conditions of pH 7, at 40°C for 10 days of incubation. The best condition preferred by the soil microorganism was under static and aerobic conditions which enhanced the microbial degradation of the crude engine oil. Addition of surfactant Tween 20 could also enhance the hydrocarbon degradation.